中小學教師換證制度之研究：體系內涵、遭遇阻力與配套措施 License Renewal System for Elementary and Secondary School Teachers: Contents, Resistance, and Supporting Measures - 吳清山 Ching-Shan Wu; 王令宜 Ling-Yi Wang; 林雍智 Yung-Chih Lin (National Taiwan Normal University, 2021)
教師專業能力的提升與教育品質的保障息息相關，因此也成為國際重視的重要議題，透過實施教師換證制度，定期更新教師所需之專業知識，不但有助於教師提升專業能力，也能獲得社會各界信任。本研究旨在探討中小學教師換證制度之內涵、可能遭遇阻力及配套措施，研究方法採用問卷調查方法，以學者專家、教育行政人員及學校教育人員為對象進行研究。本研究結論包含：一、換證能夠有效增進教師專業知能、維持專業水準和確保教學品質；二、換證週期以10年為最合適；三、換證採計條件以研習進修時數占多數；四、免除換證條件以獲得政府或民間團體舉辦之全國性特殊優良教師獎占多數；五、延緩證照更新條件，贊成換證期間內因生產、育嬰、侍親等事由辦理留職停薪者占多數；六、主政核發單位，贊成教育部者占多數；七、換證辦理單位贊成地方政府研習機構者占多數；八、推動換證遭遇之阻力，最主要為缺乏法源依據；九、推動換證之配套措施，主要為將換證明定於《教師法》內，取 得法源依據。根據上述結論，本研究再提出若干建議，供規劃及推動中小學教師換證體系之參考。 Enhancing teachers' professional abilities is closely related to ensuring high education quality and has become a key educational issue globally. Teacher license renewal (TLR) systems not only benefit teachers' professional learning but enable them to gain social trust. This study explored the contents of and resistance to implementing TLR; the study also evaluated the system for supporting TLR for elementary and secondary school teachers in Taiwan. This study was conducted using questionnaires administered to scholars, educational administrators, and school educators. Nine conclusions were drawn: (1) TLR can effectively function to enhance the professional knowledge, maintain the professional standards, and ensure the quality of teachers. (2) The TLR cycle period should be 10 years. (3) Training hours are the main consideration of TLR. (4) Most participants agreed that the Nationwide Special Excellent Teacher Awards should be accepted as an exemption to license renewal. (5) TLR should be postponable for childbirth, childcare, or paternity. (6) The Ministry of Education should be the license-issuing authority. (7) The TLR training hours should mainly include those at local government training institutes. (8) The main difficulty of promoting TLR is the lack of a legal basis. Finally, (9) the main measure proposed for supporting TLR is to amend the "Teacher Law" to obtain the legal basis. A discussion of the implications these concrete suggestions for promoting TLR is presented.